Effects of Nutrient Addition on Pedicularis kansuensis Invasion of Alpine Grassland - Haining Li; Yanming Gong; Fei Fang; Kaihui Li; Yanyan Liu (Atmosphere, 2023)
In order to study the changes in invasive plant population characteristics under different nutrient addition treatments, this study used the native invasive species Pedicularis kansuensis, which is spreading in the Bayabulak alpine grassland, as the research object and conducted two consecutive years of field studies in which nutrients were added to plots. Changes in the P. kansuensis population’s invasive characteristics were monitored in 2020 and 2021 in four different nutrient-addition treatments, namely no-nutrients (control), low-nitrogen, high-nitrogen, and phosphorus treatments. The result showed that (1) nutrient addition had significant effects on P. kansuensis height and root/shoot ratio (p < 0.05); the time effect had significant effects on P. kansuensis height, coverage, abundance, aboveground biomass, and belowground biomass (p < 0.01), and the interaction between nutrient addition and time had a significant effect on P. kansuensis height (p < 0.01). (2) Nitrogen addition effectively inhibited the growth and the development of P. kansuensis, especially under high-nitrogen conditions in the second growing season, where the effect of height (2.50 cm), coverage (0.13%), richness (3 strains), aboveground biomass (0.21 g m−2), and belowground biomass (0.03 g m−2) was significant, with the P. kansuensis population almost disappearing by the end of the trial. (3) Phosphorus addition had no significant effect on the P. kansuensis population’s invasive characteristics. These results indicate that higher nitrogen addition could effectively slow the invasion of the P. kansuensis population, and the findings of this study could provide certain baseline data and scientific guidance for the effective control of the P. kansuensis invasion of the Bayabulak alpine grassland in the future as well as identify certain theoretical bases for the effect of nutrient addition on invasive plants overall.